ADVANCEMENT OF E-PORTFOLIO SYSTEM TO IMPROVE COMPETENCE LEVELS - Gorbunovs, Aleksandrs; Kapenieks, Atis; Kudina, Ieva (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Nowadays educational process is not imaginable without applications of information technologies. Their implementations in different technology enhanced learning programs, platforms and systems are becoming more and more popular in educational institutions all over the world. Appropriate usage of information systems has already gained significant place in curriculums and learning processes. However, due to rather high dropout rate and insufficient learning outcomes educational organisations are still seeking for new systems, tools and methods which would enhance learners’ competence development. This paper describes benefits of a new ePortfolio system created by Riga Technical University’s researchers group, its testing results in Living Lab environment in study year 2012/2013, and comparative analysis with initial version of the system implemented in previous year. Findings show that introduced new ePortfolio system has a great positive impact on learning outcomes and learners’ competence development.